Micromagnetic Simulation of La0.7Sr0.3MnO3 (LSMO) Nano Disk by Finite Element Methods - Rohman, L.; Sugihartono, I.; Nursiyanto, W.; Djuhana, D.; Soegijono, B. (Jurnal Spektra, 2013)
This researched have been studied the LSMO nanodisk with the various of thicknesses are t=5nm,10nm and 15 nm. The diameter of the nanodisk is constant with the magnitude D=100nm.  This researched have done the micromagnetic simulations by finite element method.  The finite element method (typically) subdivides space into many small tetrahedra. The tetrahedra are sometimes referred to as the (finite element) mesh elements. While the finite difference method subdivides space into many small cuboids.  Finite element simulations are best suited to describe geometries with some amount of curvature, thus the disk (cylindrical) shape is approximated better than with the finite differences.   The hysteresis loops shown the barkhausen jump phenomenon in the thickness of nanodisk with t=15 nm, D=100nm. This phenomenon relates to the energy profile of the systems. The energy profile of the nanodisk LSMO systems with different thicknesses is dominated by demagnetization energy. This means that the domain structures of the nanodisk are dominated by single domain.  The coercive fields of the hysteresis curve are shown the values:  10.5 mT, 7.5 mT and 1.5 mT for the relation to thickness of the nanodisk t=5nm, t=10nm and t=15nm.Keywords: Micromagnetic simulations, LSMO (La0.7Sr0.3MnO3), nanodisk,finite element methods,barkhausen jump, coercivity field, demagnetization energy, and energy profile.